2009
DOI: 10.1177/1069072708330678
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Career Decision-Making Course

Abstract: This study examined the effectiveness of a college career course designed to increase career decision-making confidence and facilitate career exploration. Participants were 73 students from a large Midwestern university (65.6% women, 34.4% men, mean age 18.56). Students were given questionnaires assessing career decision-making difficulties, career decision-making self-efficacy, and perception of career and educational barriers during the first and fifteenth weeks of the course. Repeated measures analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 26 publications
5
81
0
3
Order By: Relevance
“…Results supported our Hypothesis A well as ambiguity tolerance was found to be predictive of the four domains of general indecisiveness, dysfunctional beliefs, lack of information, and inconsistent information. As previous research showed (Fouad, Cotter, & Kantamneni, 2009;Gati, et al, 2013), general indecisiveness and dysfunctional beliefs could not be relieved by simply acquiring more information, suggesting that they are more chronic issues and need an adjustment on the characteristic information processing style. The current result is resonant with these arguments that how people handle the ambiguity is closely associated with the issues of general indecisiveness and dysfunctional beliefs.…”
Section: Discussionmentioning
confidence: 71%
“…Results supported our Hypothesis A well as ambiguity tolerance was found to be predictive of the four domains of general indecisiveness, dysfunctional beliefs, lack of information, and inconsistent information. As previous research showed (Fouad, Cotter, & Kantamneni, 2009;Gati, et al, 2013), general indecisiveness and dysfunctional beliefs could not be relieved by simply acquiring more information, suggesting that they are more chronic issues and need an adjustment on the characteristic information processing style. The current result is resonant with these arguments that how people handle the ambiguity is closely associated with the issues of general indecisiveness and dysfunctional beliefs.…”
Section: Discussionmentioning
confidence: 71%
“…Pervious research found the CDMP to be highly stable over a one-year period, with a median within-participant correlation of .81 across the 12 dimensions (Gati & Levin, 2012), whereas research on the CDDQ found that intervention reduces career decision-making difficulties (Fouad, Cotter, & Kantamneni, 2009;Perdrix, Stauffer, Masdonati, Massoudi, & Rossier, 2012), indicating that this construct is more situational. Therefore, in the current study we hypothesized that the CDMP scores would predict the CDDQ scores, and not the other way around.…”
Section: Cross-cultural Analysis Of Career Decision Making 10mentioning
confidence: 98%
“…There is clear evidence linking self-efficacy theory to career development amongst college students (Burns, Jasinski, Dunn, & Fletcher, 2013;Fouad, Cotter, & Kantamneni, 2009;Scott & Ciani, 2008). A similar approach might also promote healthy psychosocial development.…”
Section: Ecological Map For the Athletic Well-being Modelmentioning
confidence: 99%